Analysis of Drawings on Representations of COVID-19 among Senior High School Students: Case of the Dakhla-Oued Eddahab Region, Morocco - Lhoussaine Maskour; Bouchta El Batri; Sidi Mohamed Oubit; Eila Jeronen; Boujemaa Agorram; Rahma Bouali (MDPI AG, 2022)
Since the coronavirus COVID-19 was identified as an international public health emergency in 2020, many studies on the perceptions of students in higher education have been published concerning it. Although young students' perceptions also influence decision making and actions, their perceptions of COVID-19 have, so far, been little studied. Therefore, to increase knowledge about their understanding of COVID-19, a cross-sectional and descriptive study was conducted as a drawing survey in two schools in the Dakhla-Oued Eddahab region, Morocco. The participants were 94 high school students (aged 14-19). The drawings were analyzed by inductive and deductive content analysis. The findings show that the majority of the students knew the archetypal representation of COVID-19. They had a good grasp of the COVID-19, how it spreads, and how to stop it from spreading. Some students were aware of the potential dangers associated with COVID-19. Admittedly, misrepresentations related to fear and unfamiliarity with COVID-19 lead to mental health issues that undermine the key factors in students' academic success. Younger children's representations were dominated by magical thinking that reduces COVID-19 to preventive measures. Overall, the results made it possible to deduce that COVID-19 is strongly associated with terms that are both characteristic and socially valued (disease, prevention, barrier measures, etc.) and, conversely, with rather negative terms (fear of dying, anxiety, sadness, helplessness, etc.). The identification of these representations is very useful because they make it possible to apprehend and understand the attitudes and behaviors of these students, which, therefore, implies the need to define the appropriate teaching methods to try to align these behaviors with the behaviors desired.